Programme Evaluation and Treatment Choice - Frölich, Markus (Springer Berlin Heidelberg, 2003)
Policy evaluation and programme choice are important tools for informed decision-making, for the administration of active labour market programmes, training programmes, tuition subsidies, rehabilitation programmes etc. Whereas the evaluation of programmes and policies is mainly concerned with an overall assessment of impact, benefits and costs, programme choice considers an optimal allocation of individuals to the programmes. This book surveys potential evaluation strategies for policies with multiple programmes and discusses evaluation and treatment choice in a coherent framework. Recommendations for choosing appropriate evaluation estimators are derived. Furthermore, a semiparametric estimator of optimal treatment choice is developed to assist in the optimal allocation of participants
Keywords: Econometrics; Economic Policy; Statistics for Business, Management, Economics, Finance, Insurance; Economic policy; Statistics; Schätztheorie; Ökonometrisches Modell; Wirkungsanalyse; Politisches Programm; Wirtschaftspolitik; Arbeitsmarktpolitik; Nichtparametrische Schätzung; Politische Entscheidung; Hochschulschrift